STABILITAS EKSTRAK WARNA BUNGA ASOKA (Ixora javanica) BERDASARKAN VARIASI pH SELAMA MASA PENYIMPANAN - ellditna jenianti; Nurhaeni; Pasjan Satrimafitrah; Dwi Juli Pusptasari (KOVALEN: Jurnal Riset Kimia, 2019)
Research on the potential of Ashoka (Ixora javanica) flower as a natural food and beverage coloring agent in terms of pH stability during the storage period. This study aims to determine the stability of Asoka flower extract on the effect of pH during the storage period. The time used was 10 days and the variation of pH of 2,3,4,5 and 6, respectively. The results show that Asoka flower extract was stable at pH 2 after a 10-day storage period with degradation presentation of 36.21%, while Ashoka flower extract dyes were unstable at pH 6 after a 10-day storage period with degradation percentage is 78.02%. This proves that the different acidic atmosphere influences the stability of Ashoka flower extract. Keywords : Dyes, stability of Ashoka flowers, degradation